2004
DOI: 10.1517/14740338.3.6.655
|View full text |Cite
|
Sign up to set email alerts
|

Impact of phenytoin therapy on the skin and skin disease

Abstract: Phenytoin (diphenylhydantoin; Dilantin), ALZA Corp.) is a highly effective and widely prescribed anticonvulsant agent used in the treatment of focal and tonic clonic generalised seizures. The side effects of phenytoin can occassionally engender significant morbidity. Phenytoin can induce generalised eruptions that include: a maculopapular exanthem, Stevens-Johnson syndrome, generalised exfoliative dermatitis, toxic epidermal necrolysis, vasculitis and fixed drug eruptions. Phenytoin is linked to a hypersensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 103 publications
0
10
0
1
Order By: Relevance
“…29 These compounds exhibited improved activity against a number of resistant isolates including the MLS b (macrolide-lincosamides-group B streptogramine resistant) bacteria and demonstrated that the 3- O -cladinose was not necessary for activity. 28,29 …”
Section: Resultsmentioning
confidence: 99%
“…29 These compounds exhibited improved activity against a number of resistant isolates including the MLS b (macrolide-lincosamides-group B streptogramine resistant) bacteria and demonstrated that the 3- O -cladinose was not necessary for activity. 28,29 …”
Section: Resultsmentioning
confidence: 99%
“…Parentral exposure to phenytoin may result in a spectrum of structural, developmental and behavioural changes, known as fetal hydantion syndrome. 9 Erythroderma is a state of severe skin disease. The clinical manifestations are erythematic with inflammatory skin disease, scaling on the cutaneous surface of the skin, thickened skin, itching, swollen lymph nodes, fever and finally it may lead to dehydration (loss of fluids and proteins).…”
Section: Discussionmentioning
confidence: 99%
“…• Hábitos: a linfadenopatia pode ser secundária ao uso de fenitoína ou isoniazida 10 . Resposta a antibióticos específicos também pode ajudar a confirmar ou afastar diagnósticos 1,10 .…”
Section: Anamneseunclassified